Grupa VAT – istotnym elementem pakietu Polskiego Ładu : analiza korzyści, zasad funkcjonowania oraz ryzyk związanych z jej utworzeniem - Konieczna-Kłobut, Katarzyna (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2020)
On 26 July 2021 on the website of the Government Legislation Centre appeared a draft of the Minister of Finance, Funds and Regional Policy regarding the Act on amending the Law on personal income tax, the Law on corporate income tax and some other laws - including the Law on tax on goods and services. Subsequently, on 8 September the partially amended version of the draft was submitted to the Sejm (print no.: 1532). The idea behind the changes in VAT is to make it even more competitive - and one of its main assumptions is the long-awaited introduction of an optional possibility to create the so-called VAT group. The main idea of the VAT group is to keep the intra-group turnover neutral or not to issue invoices. This may be of particular benefit where some of the taxpayers in the group do not have the full right to deduct input VAT or have an excess of output VAT, while others deduct VAT in full or have an excess of input VAT. The idea of creating a VAT group is therefore undoubtedly a positive one, but the key issue remains the conditions for its creation in order for this model to be workable for Polish VAT taxpayers.
Keywords: VAT; VAT Group; Polish Order; VAT tax